Empowering the lowland indigenous community through child health and nutrition program in Occidental Mindoro Province, Philippines - Gonzales, Artemio Morado, Jr (ASEAN Journal of Community Engagement, 2020)
Nutrition and child health programs were integrated into the extension programs from 2016-2018 of the Occidental Mindoro State College, in partnership with the local government unit at the municipal and barangay levels. This paper presents the health extension tools and techniques used in preventative care and the promotion of child health services in the indigenous community of Sitio Bato Singit, in the Occidental Mindoro Province, Philippines. Health education, small group techniques, demonstrations, storytelling, informal talks, and open forums were the methods and techniques employed to implement the program. The common tools used were seating arrangements, flip-charting, props, social hours, and recreation. In terms of the evaluation of the program, child health outcomes remain poor, despite the efforts of the different blocks working within the health system. These programs could enhance their health knowledge and practices in other extension modalities.